Investigating inter-league and inter-nation variations of key determinants for penalty success across European football - Jamil, M.; Littman, P.; Beato, M. (International Journal of Performance Analysis in Sport, 2020)
The aim of this study was to investigate the inter-league and inter-nation variations of key performance, situational and individual variables on penalty success across four elite European football leagues. A sample of 1,716 penalty kicks taken in four consecutive seasons (2015/16 - 2018/19) were analysed via a series of bootstrapped regressions. Results revealed that penalty success in each country depends upon; the length of the run up, the direction of the strike, the type of strike, which foot the penalty is struck with, match status, time periods and venue, but to varying extents in each league. Penalty takers in the English Premier League aimed centrally (p = 0.003) whereas penalty kicks were aimed towards the bottom corners in the Spanish La Liga (p = 0.009), German Bundesliga (p = 0.004) and Italian Serie A (p = 0.004). Inter-nation variations were also discovered between classes of variables associated with the length of the run-up, the type of strike, which foot the penalty is struck with, match status, time periods and venue. The authors conclude that penalty takers should pay special attention to the inter-league variations discovered in this study in order to further inform their penalty strategies and enhance their levels of unpredictability, ultimately increasing their penalty proficiency.